The Sacrificial Rituals of Greek Hero-Cults in the Archaic to the Early Hellenistic Period - Gunnel Ekroth (Presses universitaires de Liège, 2002)
This study questions the traditional view of sacrifices in hero-cults during the Archaic to the early Hellenistic periods. The analysis of the epigraphical and literary evidence for sacrifices to heroes in these periods shows, contrary to the traditional notion, that the main ritual in hero-cults was a thysia at which the worshippers consumed the meat from the animal victim. A particular handling of the animal's blood or a holocaust, rituals previously taken to be typical for heroes, can rare...